Parental Notification Via Text Messaging for Infant Sickle Screening Programs: Exploration of Feasibility and Acceptability in Uganda. Issue 7 (October 2020) - Fashakin, Victoria; Mathur, Sanyukta; Kwagala, Peter; Mupere, Ezekial; Kiguli, Sarah; Kitaka, Sabrina B.; Henry, Michael B.; Van Ells, Luke; Tusuubira, Sharifu; Mulumba, Lukia; Duong, Jimmy; Stockwell, Melissa S.; et al.
Abstract : Sickle cell disease (SCD) in Africa has high prevalence, morbidity, and early mortality. Difficulties in reaching parents following infant SCD screening dampen program effectiveness. Text messaging may support initial postscreening parental notification. We explored SCD awareness, and feasibility and acceptability of text messaging about screening follow-up among convenience samples of caretakers with children under 5 years (n=115) at 3 sites: a SCD family conference or 2 general pediatric clinics in urban or rural Uganda. Two thirds of the conference-based participants and 8% at clinic sites had affected children. At the clinics, 64% of caretakers were aware of SCD. In all, 87% claimed current possession of mobile phones; 89% previously had received messages. A sample text on the availability of screening results and need to bring their child to SCD clinic was at least partially understood by 82%. Overall, 52% preferred communication for initial follow-up by telephone over text message. Concerns about texting included phone access, privacy or cost, and readability of messages. Caretakers identified concerns about distance, cost, or preference for another clinic as additional barriers to SCD follow-up. Findings suggest that text messaging to caretakers may be feasible, but less acceptable compared with a telephone call about initial follow-up from newborn SCD screening.